1981
DOI: 10.3322/canjclin.31.5.300
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Asymptomatic Women for Endometrial Cancer

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
27
0
2

Year Published

1985
1985
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 3 publications
1
27
0
2
Order By: Relevance
“…However, currently routine screening for endometrial cancer is not recommended in asymptomatic women, either for the premenopausal [14] or the postmenopausal population [2,5,6]. Some of the main justifications against its utilization are the poor positive predictive value of TVUS and the low incidence of endometrial cancer in asymptomatic postmenopausal women [15,16,17,18]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, currently routine screening for endometrial cancer is not recommended in asymptomatic women, either for the premenopausal [14] or the postmenopausal population [2,5,6]. Some of the main justifications against its utilization are the poor positive predictive value of TVUS and the low incidence of endometrial cancer in asymptomatic postmenopausal women [15,16,17,18]. …”
Section: Discussionmentioning
confidence: 99%
“…A study by Koss et al [15] in 1981 screened 1,280 asymptomatic women aged 45 and older with endometrial sampling. Among them, 1,088 (85%) were postmenopausal and there were only 8 confirmed carcinoma cases (0.6%).…”
Section: Discussionmentioning
confidence: 99%
“…17,18 The cystic dilation of endometrial glands and the amount of intervening stroma between glands are the most important parameters for classifying cystic and adenomatous hyperplasias, respectively. However, it is important to recognize that these are histologic, and not cytologic, parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that endometrial carcinoma may be diagnosed incidentally in asymptomatic women. [2][3][4][5][6] Most of these observations are only anecdotal. There has been only 1 large cohort study on endometrial screening in asymptomatic women 13 : a cohort of 2,586 asymptomatic women was screened and an incidence of 6.96 per 1,000 reported.…”
Section: Discussionmentioning
confidence: 99%
“…[2][3][4][5][6] Neither the staging of patients nor their outcome is mentioned, even in large cohort studies. 2,3 The aim of this study was to assess whether screening asymptomatic women is significant for the early detection of endometrial carcinoma. The mean age of the 21 asymptomatic patients was 51.2 years (range, 33-78), while that of the 421 symptomatic patients was 53.9 (24-83), revealing no significant difference.…”
mentioning
confidence: 99%